Introduction of α-MnO2 nanosheets to NH2 graphene to remove Cr6+ from aqueous solutions1. Issue 55 (17th June 2015) - Zhang, Li; Tian, Yaxi; Guo, Yaopeng; Gao, Hui; Li, Haizhen; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> The planar structure of the designed α-MnO2–NH2–RGO hybrid was prepared and characterized and used to remove hexavalent chromium ions (Cr6+) from aqueous solutions.